Mondo, natura, tecnica - Ardovino, Adriano (Bollettino Filosofico, 2023)
Whether thought in terms of irreducible opposition, or in terms of co-belonging and even of identification, the nexus between “nature” and “technology” has often been unfolded by philosophical reflection in dichotomous terms, i.e. on the basis of a two-term theory. Exceptions are speculative projects, such as those of Hegel and Heidegger, who for his part in the Bremen Lectures (1949) deals with the “nature-technology” nexus on the basis of a third term, i.e. the “world”, capable of reorganizing and redefining this nexus in depth. The present article aims at bringing out such a peculiar framework in its essential features. Keywords: Ereignis, Heidegger, Nature, Technology, World